2D Ruddlesden–Popper Perovskites Microring Laser Array. Issue 15 (8th March 2018) - Zhang, Haihua; Liao, Qing; Wu, Yishi; Zhang, Zhaoyi; Gao, Qinggang; Liu, Peng; Li, Meili; Yao, Jiannian; Fu, Hongbing
Abstract: 3D organic–inorganic hybrid perovskites have featured high gain coefficients through the electron–hole plasma stimulated emission mechanism, while their 2D counterparts of Ruddlesden–Popper perovskites (RPPs) exhibit strongly bound electron–hole pairs (excitons) at room temperature. High‐performance solar cells and light‐emitting diodes (LEDs) are reported based on 2D RPPs, whereas light‐amplification devices remain largely unexplored. Here, it is demonstrated that ultrafast energy transfer along cascade quantum well (QW) structures in 2D RPPs concentrates photogenerated carriers on the lowest‐bandgap QW state, at which population inversion can be readily established enabling room‐temperature amplified spontaneous emission and lasing. Gain coefficients measured for 2D RPP thin‐films (≈100 nm in thickness) are found about at least four times larger than those for their 3D counterparts. High‐density large‐area microring arrays of 2D RPPs are fabricated as whispering‐gallery‐mode lasers, which exhibit high quality factor ( Q ≈ 2600), identical optical modes, and similarly low lasing thresholds, allowing them to be ignited simultaneously as a laser array. The findings reveal that 2D RPPs are excellent solution‐processed gain materials potentially for achieving electrically driven lasers and ideally for on‐chip integration of nanophotonics. Abstract : Room‐temperature 2D Ruddlesden–Popper perovskite (RPP) amplified spontaneous emission and lasing are achieved by ultrafast energy transfer along the cascade quantum well to concentrate on the lowest‐bandgap quantum well for population inversion. High‐density large‐area microring arrays of 2D‐RPPs are fabricated as whispering‐gallery‐mode lasers with high quality factor, identical optical modes, and similarly low lasing threshold.